2007
DOI: 10.1002/hyp.6619
|View full text |Cite
|
Sign up to set email alerts
|

Simulating soil‐water movement under a hedgerow surrounding a bottomland reveals the importance of transpiration in water balance

Abstract: The objective of this study was to quantify components of the water balance related to root-water uptake in the soil below a hedgerow. At this local scale, a two-dimensional (2D) flow domain in the x-z plane 6 m long and 1*55 m deep was considered. An attempt was made to estimate transpiration using a simulation model. The SWMS-2D model was modified and used to simulate temporally and spatially heterogeneous boundary conditions. A function with a variable spatial distribution of root-water uptake was considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…The driving force is the deep tree root system that can lift water from wet soil horizons several meters below the ground up to the leaves (Richards and Caldwell, 1987; Ryszkowski and Kedziora, 1993). It is recognized that trees have higher transpiration rates and greater influence on soil water transfer than other plants (Thomas et al , 2008), resulting in reduced surface runoff, groundwater recharge, and interflow (Cosandey, 2001) and, in some cases reverse the hydraulic gradient underneath them (Heuperman, 1999). Trees are able to adapt their water use to local soil water conditions and hence optimize their water uptake to use the available water in their root zone efficiently (Plamboeck et al , 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The driving force is the deep tree root system that can lift water from wet soil horizons several meters below the ground up to the leaves (Richards and Caldwell, 1987; Ryszkowski and Kedziora, 1993). It is recognized that trees have higher transpiration rates and greater influence on soil water transfer than other plants (Thomas et al , 2008), resulting in reduced surface runoff, groundwater recharge, and interflow (Cosandey, 2001) and, in some cases reverse the hydraulic gradient underneath them (Heuperman, 1999). Trees are able to adapt their water use to local soil water conditions and hence optimize their water uptake to use the available water in their root zone efficiently (Plamboeck et al , 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Hedgerow (Acer campestre) transpiration rates have been observed reaching peak values of 8 mm day 1 (Herbst et al, 2007). The large impact of hedgerows on soil-water balance is due to their high transpiration rate (Thomas et al, 2008). Comparing simulated and observed results, Ticehurst et al (2005) identified several dominant processes to include in a simulation model to take into account the effect of tree belts on hillslopes: evaporation, surface runoff, lateral flow, and vertical drainage.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the LF within the root zone from top to bottom was trivial, which might be explained by the small elevation difference or rainfall intensity [40,41], or lack of a headwater catchment [24]. Thus, further work is needed to quantify the response of LF to altered precipitation intensity and sand-fixing shrub density in dune-interdune landscapes, which would contribute to water resource management.…”
Section: Effect Of Micro-topography On Hydrological Budgetsmentioning
confidence: 85%
“…Numerical simulation is a flexible and cost-efficient alternative and approximates the hydrological system using computational models. Some scholars have applied mechanistic models such as HYDRUS, SWMS, and APRI to investigate the hillslope hydrological mechanisms related to the management of water resources [24][25][26]. However, to our knowledge, there has been no research on predicting hydrological processes in the dune-interdune landscape in the Horqin Sandy Land using hydrological models.…”
Section: Introductionmentioning
confidence: 99%